Hubungan Kemampuan Matematika dan Kemampuan Awal dengan Hasil Belajar Kimia Siswa SMA Kelas XI pada Pokok Bahasan Larutan Penyangga - Pasar Maulim Silitonga; Freddy Tua Musa Panggabean; Nora Susanti; Marudut Sinaga; Lesrida Situmorang (Jurnal Inovasi Pembelajaran Kimia (Journal Of Innovation in Chemistry Education), 2022)
Chemistry is one of the most difficult subjects for most students. There are many factors that influence the success of students in learning chemistry, including mathematical abilities and students' initial abilities. This study aims to determine the relationship between mathematical ability and initial ability with students' chemistry learning outcomes. The sample of this study consisted of one class, namely class XI IPA 2 students who were taken by random sampling technique. Data analysis used simple regression test with variance test (variance fingerprint) and multiple regression, as well as correlation test and coefficient of determination at a significance level of 5%. The results showed that (1) there was a significant relationship between mathematical ability and student chemistry learning outcomes, with a contribution of 16%; (2) There is a significant relationship between initial ability and student chemistry learning outcomes, with a contribution of 33.64%; (3) There is a significant relationship between mathematical ability and initial ability simultaneously with student chemistry learning outcomes with a coefficient of determination of 51.27%.Ilmu kimia merupakan salah satu pelajaran tersulit bagi kebanyakan siswa. Ada banyak factor yang mempengaruhi keberhasilan siswa dalam belajar kimia, diantaranya kemampuan matematika dan kemampuan awal siswa. Studi ini bertujuan untuk mengetahui hubungan kemampuan matematika dan kemampuan awal dengan hasil belajar kimia siswa. Sampel penelitian ini terdiri dari satu kelas yaitu siswa kelas XI IPA 2 yang diambil dengan teknik random sampling. Analisis data menggunakan uji regresi sederhana dengan uji varians (sidik ragam) dan regresi ganda, serta uji korelasi dan koefisien determinasi pada taraf signifikasi 5%. Hasil penelitian menunjukkan bahwa (1) Ada hubungan yang signifikan antara kemampuan matematika dengan hasil belajar kimia siswa, dengan kontribusi sebesar 16%; (2) Ada hubungan yang signifikan antara kemampuan awal dengan hasil belajar kimia siswa, dengan kontribusi sebesar 33,64%; (3) Ada hubungan yang signifikan antara kemampuan matematika dan kemampuan awal secara simultan dengan hasil belajar kimia siswa dengan koefisien determinasi sebesar 51,27%.